Mobilization of Saving in Developing Countries : The Case If the Islamic Republic of Iran - El-Erian, Mohamed (IMF Working Papers; Working Paper ;, 1996)
Mobilization of national saving is an important determinant of investment and growth. It assumed greater importance in the case of the Iranian economy, given the difficult external environment. This paper discusses the recent saving performance of the Iranian economy, particularly in relation to investment needs. Following a quantitative evaluation of the determinants of saving, the paper reviews the main implications for domestic economic policies in the period ahead.